Analysis of Conflict Management and Industrial Relations Dispute Resolution Case In Central Java - Aditya Maulana Maulana; Retno Kurniasih Kurniasih; Bahtiar Efendi Efendi (International Journal Business and Entrepreneurship, 2025)
This study examines conflict management and dispute resolution in industrial relations in the Central Java region, Indonesia, using a qualitative case study approach. Primary data were collected from 20 in-depth interviews and 10 participatory observation sessions involving 25 key informants, including business owners, labor union representatives, professional mediators, and officials from the Department of Manpower. Secondary data were obtained from official documents as well as the annual reports of the Central Java Department of Manpower. The purpose of the study is to identify the interpretative and procedural obstacles in implementing Law No. 2 of 2004, and to assess the role of digital technology, ethical values, and transformational leadership in improving the mediation process. The findings indicate significant differences between the urban industrial sector and micro enterprises in rural areas, resulting in inefficiencies in conflict resolution. Additionally, the study found that the limited flow of information among stakeholders leads to miscommunication and a decrease in trust. The implementation of digital platforms in several companies in Semarang has been shown to enhance transparency and expedite communication processes. Moreover, transformational leadership that emphasizes open dialogue and active participation is deemed crucial in reducing conflict escalation. The practical implications of this research include enhancing mediator capacity through comprehensive training, developing integrated digital mediation infrastructure, and standardizing the interpretation of regulations. These findings contribute significantly to the development of holistic conflict resolution policies at both regional and global levels.